Pengaruh Produk Domestik Bruto dan Inflasi Terhadap Jumlah Uang Beredar (M1) di Indonesia Periode 1980 – 2020 Menurut Pendekatan Klasik - Arkan Daffa Ghalib; D. Damayanti; Widy Shity Nur Shava (Universitas Warmadewa, 2023)
The The research aims to determine the effect of gross domestic product (GDP) and inflation on the total money supply (JUB) in Indonesia. This study uses timeseries data from 1980 to 2020 obtained from the Central Bureau of Statistics, and Bank Indonesia. This study uses a classical approach. The research was conducted using multiple linear regression. Hypothesis testing using the t test and f test is used to determine the feasibility of the model. The results of the analysis show that the Gross Domestic Product Variable (X1) partially has a positive and significant effect on the Money Supply in Indonesia. The Inflation Variable (X2) partially influences the Money Supply in Indonesia. Based on the analysis of the Simultaneous Test value prob. F of 0.00 < error rate of 0.05. Thus, Ho is rejected and H1 is accepted. This shows that the Gross Domestic Product (X1) Inflation (X2), simultaneously has a significant effect on the Money Supply in Indonesia, because F count is 36.07 > 3.25 F table and the Adjusted R Square coefficient or the coefficient of determination is 0.7452 This means 74.52% of the variation or change in the total money supply can be explained by variations in Gross Domestic Product and Inflation, while the rest (25.48%) is explained by other variables outside this research model. This is consistent with the quantity theory of money. According to the quantity theory of money, according to Irving Fisher, it states that the amount in circulation is directly proportional to changes in prices.